Death of the Emissary: Language, Metonymy, and European Complicity in Juan Diego Botto's "La carta". Issue 3 (3rd July 2018) - Coleman, Jeffrey K.
Abstract: Juan Diego Botto's2005 monologue "La carta" explores the real-life death of Yaguine Koita and Fodé Tounkara, two Guinean boys who in 1999 died attempting to reach Europe with a letter addressed to European officials. A close reading of Botto's monologue illustrates how the letter by Yaguine and Fodé functions as an archive that explores and redefines the liminal spaces, and therefore the relationship, between Europe and Africa. The monologue and the letter elucidate the boys' position as emissaries who seek to reconcile the European continent with its complicity in the state of Africa.